Genetic control of a cytochrome P450 metabolism-based herbicide resistance mechanism in Lolium rigidum - Busi, R. (2011)
The dynamics of herbicide resistance evolution in plants are influenced by many factors, especially the biochemical and genetic basis of resistance. Herbicide resistance can be endowed by enhanced rates of herbicide metabolism because of the activity of cytochrome P450 enzymes, although in weedy plants the genetic control of cytochrome P450-endowed herbicide resistance is poorly understood. In this study we have examined the genetic control of P450 metabolism-based herbicide resistance in a well-characterized Lolium rigidum biotype. The phenotypic resistance segregation in herbicide resistant and susceptible parents, F1, F2 and backcross (BC) families was analyzed as plant survival following treatment with the chemically unrelated herbicides diclofop-methyl or chlorsulfuron. Dominance and nuclear gene inheritance was observed in F1 families when treated at the recommended field doses of both herbicides. The segregation values of P450 herbicide resistance phenotypic traits observed in F2 and BC families was consistent with resistance endowed by two additive genes in most cases. In obligate out-crossing species such as L. rigidum, herbicide selection can easily result in accumulation of resistance genes within individuals.